BENCHMARKING; ENHANCING THE ADVANTAGES OF LINGUISTIC COMPETITIVENESS IN ISLAMIC BOARDING SCHOOLS - Lukman Hakim; Eka Diana; Wardatus Sholihah (JURNAL AL-TANZIM, 2021)
During the Covid-19 pandemic, SMA Nurul Jadid, Probolinggo, East Java created a quality assurance system to survive and win the rivalry between educational institutions. The researcher attempts to understand the meaning behind school quality assurance operations using a qualitative with case study. Interviews with school committees, principals, vice-principals, and teachers, as well as observations and documentation, were done in this instance. Data gathering, data reduction, display, and conclusion are all steps in the data analysis process. The findings revealed that SMA Nurul Jadid's quality assurance system was implemented and evaluated through systematic planning, including numerous school members and the community, quality assurance implementation, and evaluation. This study has implications for the significance of educational institutions maintaining excellence to sustain the public trust built up over the years.